A dual-criteria flow shop scheduling with sequence-dependent setup times - Nailwal, Kewal Krishan; Gupta, Deepak; Sharma, Sameer (Journal of information & optimization sciences, 2015)
Sequence-dependent setup time is the most complicated case of setup time of jobs on machines in shop scheduling. The operational cost of machines is related to the setup time required for preparation of jobs on machines. The objective is to minimize operational cost of machines subject to minimum total elapsed time of jobs for two stage flow shop problem. The setups on both the machines for jobs are considered to be sequence-dependent. The machines having different traits processing for different jobs are attached with probabilities. In addition to this, the problem also takes the effect of breakdown interval during the operation of jobs on total elapsed time and hence on the operational cost. To solve the problem an algorithm is proposed and a numerical example is given to substantiate the algorithm.